Analysis of the teaching practice of the Department of Architecture of the National Autonomous University of Honduras Teachers - Martínez Ordóñez, Milgian Dixiana (Estoa. Journal of the Faculty of Architecture and Urbanism, 2024)
This article presents the experience of three teachers from the Department of Architecture at a public university in Honduras, with different specialties, who have planned, designed, and implemented coordinated activities in the same classroom. In this regard, the research explores the process of planning, content selection, teaching methodologies, and evaluation strategies employed by the teachers. The research is grounded in the interpretive paradigm from the perspective of educational research, and the methodological approach applied is the interpretive and non-interventionist multiple case study, selected through intentional maximum variation sampling. The results highlight the importance of these practices, where teachers learn from each other regardless of their level of experience, avoiding isolation and working together, employing diverse and innovative methods and strategies. Furthermore, these practices foster collaboration, respect, and solidarity among teachers.